Preparations of magnetic molecularly imprinted polymer for selective recognition and determination of 4-methylimidazole in soft beverage by high performance liquid chromatography - Helin Ye (Adsorption Science & Technology, 2017)
The magnetic molecularly imprinted polymers had been synthesized for the selective extraction and clean-up of 4-methylimidazole in cola, the most popular soft beverage. The magnetic molecularly imprinted polymers were prepared by means of suspension polymerization, using Fe 3 O 4 as magnetically component, 4-methylimidazole as template molecule, methacrylic acid as functional monomers, and ethylene glycol dimethacrylate as a cross-linker, initiated by 2,2′-azobisisobutyronitrile. The obtained magnetic molecularly imprinted polymers were characterized by scanning electron microscopy, Fourier transform infrared, X-ray diffraction, and vibrating sample magnetometer. High performance liquid chromatography was used for the analysis of the target analyte. The polymers were evaluated further by batch rebinding experiments. From the derived Freundlich isotherm equation, their binding capacity and binding strength were determined. Structurally similar compound and a reference compound were used for investigating the selective recognition capability of magnetic molecularly imprinted polymers. The recoveries of spiked samples ranged from 90.19 to 104.29%. The prepared magnetic molecularly imprinted polymers could be applied to selectively preconcentrate and determine 4-methylimidazole in cola samples.